Factors associated with group bullying and psychopathology in elementary school students using child-welfare facilities - Kim JW (Dove Medical Press, 2015)
Jun Won Kim,1,2 KounSeok Lee,3 Young Sik Lee,4 Doug Hyun Han,4 Kyung Joon Min,4 Sung Hwan Song,5 Ga Na Park,6 Ju Young Lee,1 Jae Ock Kim5 1Division of Child and Adolescent Psychiatry, Department of Neuropsychiatry, College of Medicine, Seoul National University, Seoul, South Korea; 2Department of Psychiatry, Graduate School, Chung-Ang University, Seoul, South Korea; 3Department of Psychiatry, Samsung Medical Center, Seoul, South Korea; 4Department of Psychiatry, Chung-Ang University, College of Medicine, Seoul, South Korea; 5Department of Psychiatry, Gongju National Hospital, Gongju, South Korea; 6Department of Special Education, Graduate School, Dankook University, Jukjeon, South Korea Purpose: Low socioeconomic status is an important risk factor for child psychiatric problems. Low socioeconomic status is also associated with psychiatric problems later in life. We investigated the effects of group bullying on clinical characteristics and psychopathology in elementary school students using child-welfare facilities.Methods: Three hundred and fifty-eight elementary school students using child-welfare facilities were recruited. The School Bullying Self Rating Questionnaire was used to assess group bullying. To evaluate related psychopathology, the Children’s Problem-Behavior Screening Questionnaire, the Children’s Depression Inventory, the Beck Anxiety Inventory, the Suicidal Ideation Questionnaire, Young’s Internet Addiction Scale, and Conners–Wells’ Adolescent Self-Report Scale were applied. Samples were classified according to school grade (lower or upper), and each group’s characteristics were compared as they related to bullying victims versus non-victims.Results: The prevalence rate of group bullying was 22% in the lower-grade group and 12% in the higher-grade group. Bullying victims in lower grades reported high somatization, depressive symptoms, Internet addiction, and attention deficit hyperactivity disorder tendencies, whereas those in upper grades reported cognitive problems, symptoms of depression and anxiety, suicidal ideation, Internet addiction, and attention deficit hyperactivity disorder tendencies. Somatization and depressive symptoms were significant predictors of bullying in the lower-grade group, and anxiety was a significant predictor of bullying in the upper-grade group.Conclusion: This study demonstrated that elementary school students using child-welfare facilities might have an increased risk of being bullied and that bullying victims may have different psychopathologies depending on their ages. Keywords: socioeconomic status, somatization, depression, anxiety